Vanillin Improves and Prevents Trinitrobenzene Sulfonic Acid-Induced Colitis in Mice - Wu, Shih-Lu; Chen, Jaw-Chyun; Li, Chia-Cheng; Lo, Hsin-Yi; Ho, Tin-Yun; Hsiang, Chien-Yun (The Journal of pharmacology and experimental therapeutics, 2009)
Inflammatory bowel disease (IBD) is chronic inflammatory and relapsing disease of the gut. It has been known that activation of nuclear factor-κB (NF-κB) and production of proinflammatory cytokines play important roles in the pathogenesis of IBD. In this study, the effect of vanillin (4-hydroxy-3-methoxybenzaldehyde), a potent nuclear factor-κB (NF-κB) inhibitor, was evaluated in mice with trinitrobenzene sulfonic acid (TNBS)-induced colitis. Oral administration of vanillin improved macroscopic and histological features of TNBS-induced colitis in a dose-dependent manner. Vanillin not only prevented TNBS-induced colitis but also ameliorated the established colitis. By in vivo NF-κB bioluminescence imaging, electrophoretic mobility shift assay, and Western blot, we found that vanillin suppressed in vivo NF-κB activities through the inhibition of p65 translocation, inhibitor of nuclear factor-κB(IκB)-α phosphorylation, and IκB kinase activation. Furthermore, vanillin reduced the expressions of proinflammatory cytokines [interleukin (IL)-1β, IL-6, interferon-γ, and tumor necrosis factor-α] and stimulated the expression of anti-inflammatory cytokine (IL-4) in colonic tissues. In conclusion, this work identified vanillin as an anti-inflammatory compound with the capacity to prevent and ameliorate TNBS-induced colitis. Due to its safety, vanillin could be a potent candidate for the treatment of IBD.